An Analysis on the Management of Septage Disposal in Mashhad and Providing a Suitable Practical Solution - Rezvan Salajegheh; Mehdi Raei Naei; Kazem Esmaili (آب و توسعه پایدار)
Septage refers to wastewater that has been concentrated after being stored in absorption wells and septic tanks. Due to the retention and storage process, its quality differs somewhat from raw wastewater entering sewage treatment plants. In the past, this type of wastewater was disposed of by direct discharge in non-residential areas or even onto vegetable farms. Septage cannot be equated with raw wastewater, as its degree of concentration and stabilization varies depending on its source, duration, and storage conditions. Therefore, proper assessments should be conducted regarding the management of its discharge into the environment. In this study, to explore the management methods for septage in the city of Mashhad, the qualitative and quantitative characteristics of Mashhad's septage were first examined. Qualitative investigations into the subject of septage revealed that studies on the quality and composition of septage have been conducted in other parts of the country too. Additionally, the standards and regulations for the disposal and treatment of septage, as well as the treatment processes themselves, were reviewed. Moreover, given the similarities between the processing of septage and the sludge from wastewater treatment plants, this process was thoroughly examined. The results of the investigation indicated that, for the liquid portion, independent treatment before discharge into surface waters is the preferred process, while composting is the most suitable approach for managing the sludge portion.